Pengaruh Perlindungan Kerja terhadap Kinerja Pekerja Migran Indonesia asal Jawa Tengah di Kota Taichung Taiwan - Hani Atul Masrifah; Sri Isnowati (Commodities, Journal of Economic and Business, 2026)
This study aims to analyze the impact of job protection, legal protection, social protection, and economic protection on the performance of Indonesian Migrant Workers from Central Java working in Taichung City, Taiwan, who are registered with the Indonesian Migrant Workers Protection Agency (BP2MI). The study also aims to provide empirical evidence on the role of each type of protection in improving the performance of Indonesian Migrant Workers. This study uses a quantitative method with an associative approach. The research was conducted online (questionnaire survey) with Indonesian migrant workers (PMI) working in Taichung City, Taiwan. The designated population is Indonesian migrant workers from Central Java working in Taichung City, Taiwan, with a population of 1,120 people. The sample in this study used a purposive sampling technique. The research sample consisted of 295 respondents who are PMIs from Central Java in Taichung City, Taiwan. Data was collected through distributing questionnaires and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R2) with the help of SPSS software. The research results show that job protection, social protection, and economic protection have a positive and significant impact on the performance of migrant workers. Meanwhile, legal protection has a significant effect but in a negative direction on migrant workers' performance. These findings indicate that improving the quality of job protection, especially in social and economic aspects, can enhance the performance of migrant workers. On the other hand, the results on the legal protection variable suggest that there is a need to evaluate the effectiveness of implementing legal protection for migrant workers in the host countries.